2021
DOI: 10.3390/su13031142
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem-Based Adaptation Practices as a Nature-Based Solution to Promote Water-Energy-Food Nexus Balance

Abstract: The objective of this study is to evaluate the contributions of ecosystem-based adaptation (EbA) practices to the water–energy–food (WEF) nexus balance, design practical pathways, and analyze barriers towards achievement of EbA-WEF balance. An area case study and descriptive methods were used to analyze data collected from 50 community forests (CFs) spread across three regions in The Gambia. Extensive information from relevant literature sources was also referred to in this study. Fourteen priority EbA practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…However, the current trends in tropical deforestation and forests degradation have jeopardized the global efforts to curb climate change and its adverse effects on ecosystems and livelihoods. Studies such as Muthee et al (2018Muthee et al ( , 2021 note anthropogenic and natural factors, such as ecosystems conversion to support livelihoods, unsustainable natural resources extraction, and wildfires, as some of the key drivers behind tropical deforestation and forest degradation.…”
Section: Brief Background On Tropical Forests Conservation and Climate Risks Managementmentioning
confidence: 99%
“…However, the current trends in tropical deforestation and forests degradation have jeopardized the global efforts to curb climate change and its adverse effects on ecosystems and livelihoods. Studies such as Muthee et al (2018Muthee et al ( , 2021 note anthropogenic and natural factors, such as ecosystems conversion to support livelihoods, unsustainable natural resources extraction, and wildfires, as some of the key drivers behind tropical deforestation and forest degradation.…”
Section: Brief Background On Tropical Forests Conservation and Climate Risks Managementmentioning
confidence: 99%
“…The review process included journal articles, working papers, technical reports, theses and book chapters. As shown in Table 1, the economic or ecosystem services for which we reviewed substantially more articles included agricultural and food outputs (11), carbon stocks within the cocoa production systems (8), and input use in Ghana s cocoa production (7). On the other hand, few relevant publications were found on some ecosystem services, and only one or two publications were reviewed.…”
Section: Datamentioning
confidence: 99%
“…Sustainable intensification, a key component of climate-smart agriculture, is also increasingly being promoted within cocoa farms as a strategy to minimize further deforestation. Climate-smart agriculture (CSA) aims to meet the triple challenge of raising agricultural productivity and farm incomes, enhancing adaptation and resilience to climate change and reducing greenhouse gas emissions from agriculture [10,11]. In addition to achieving the three objectives of CSA, agroforestry (AF) can directly benefit forest conservation.…”
Section: Introductionmentioning
confidence: 99%
“…In a study to evaluate the contributions of EbA practices to the waterenergy-food (WEF) nexus balance, Muthee et al (2021) designed practical pathways and identified barriers to achieving this balance. They analyzed data collected from 50 community forests spread across three regions in The Gambia.…”
Section: Adaptation In the Landscape: Towards Ecosystem-based Adaptat...mentioning
confidence: 99%